Molecular Identification of Lactic Acid Bacteria Producing Antimicrobial Agents from Bakasang, An Indonesian Traditional Fermented Fish Product - Lawalata, Helen Joan; Sembiring, Langkah; Rahayu, Endang Sutriswati (Indonesian Journal of Biotechnology, 2011)
AbstractTwenty seven strains of lactic acid bacteria (LAB) were isolated from bakasang, Indonesian traditional fermented fish product. In general, LAB have inhibitory activity againts pathogenic bacteria and spoilage bacteria. Screening for antimicrobia activity of isolates were performed with well-diffusion method. One isolate that was designed as Pediococcus BksC24 was the strongest against bacteria pathogenic and spoilage bacteria. This strain was further identified by 16S rRNA gen sequence comparison. Isolates LAB producing antimicrobial agents from bakasang were identified as Pediococcus acidilactici.Keywords : Bakasang, LAB, antimicrobial, phenotypic characteristics, 16S rRNA gene